Enhancement Design of Emotional Regulation of Students in Prevention of Pornographic Trends Through Information Services - Solin, Ridwan; Firman, Firman; Syahniar, Syahniar (Journal of ICSAR, 2020)
When this study was conducted, students were exposed to access to information via the internet, which negatively impacted pornography behavior. One example of media that counselors can do to improve student emotional regulation is designing guidelines for implementing attractive information services. This study aims to increase the regulation of student emotions in the prevention of pornographic tendencies through information services. This research uses research and development (R & D). The research model uses a 4-D development model. The type of data collected in this study is the type of data validity and suitability according to students' needs. The instrument of data collection in this study used a Likert scale questionnaire and group discussion. The study population was students of SMK Negeri 1 Padang. The study sample was a class XI student of SMK Negeri 1 Padang. The study results found that providing information service guidelines to improve student emotion regulation in preventing the tendency of pornography was effective in increasing the regulation of students' emotions in preventing pornographic tendencies.